Associations between shift work and use of prescribed medications for the treatment of hypertension, diabetes, and dyslipidemia: a prospective cohort study - Tucker P; Härmä M; Ojajärvi A; Kivimäki M; Leineweber C; Oksanen T; Salo P; Vahtera J (Nordic Association of Occupational Safety and Health (NOROSH)., 2022)
Objective
This study examined the associations between shift work and use of antihypertensive, lipid-lowering, and antidiabetic medications.
Methods
Survey data from two cohorts of Finnish men (N=11998) and women (N=49 944) working in multiple occupations where shift work was used were linked to national Drug Prescription Register data, with up to 11 years of follow-up. In each cohort, age-stratified Cox proportional hazard regression models were computed to examine any incident use of prescription medication for each of the three medical conditions, separately comparing each of two groups of rotating shift workers (those whose schedules included night shifts. and those whose schedules did not include night shifts) with day workers who worked in a similar range of occupations.
Results
In the larger cohort, among participants aged 40-49 at baseline, shift work without night shifts was associated with increased use of type-2 diabetes medication after adjustments for sex, occupational status, marital status, alcohol consumption, smoking, and physical activity [hazard ratio (HR) 1.28, 95% confidence interval (CI) 1.01-1.62], while shift work with night shifts was associated with increased use of dyslipidemia medication after adjustments (HR 1.33, 95% CI 1.12-1.57). There were no such associations among younger and older shift workers. Also in the larger cohort, among those aged <50 years at baseline, both types of shift work were associated with increased use of hypertension medication after adjustments [up to HR 1.20 (95% CI 1.05-1.37)]. There were no positive associations in the smaller cohort.
Conclusions
There was mixed evidence regarding the use of medications for cardiovascular risk factors by shift workers. Selection effects may have affected the associations.